The enterobacteriaceae effect in the vegetative development of corn (Zea mays) in greenhouse - Hernández, Fiorella (2015)
This research was developed with the aim of determining the effect of native enterobacteriaceae in the vegetative development of Zea mays L (corn). The yellow “corn”, under greenhouse conditions as an alternative to reduce the use of chemical fertilizers. 100 enterobacteriaceae were investigated, they were isolated from the rhizosphere of weed associated with the corn crops and characterized in vitro as plants growth promoters. In the laboratory, the native enterobacteriaceae were quantified to 1,03 – 30,21 ppm of fixed nitrogen as ammonia; 1,03 – 30,21 ppm indole acetic acid and 1,00 – 4,05 ppm solubilized phosphorus. These enterobacteriaceae were grown with nutrient agar at 30° C for 24 hours, it obtained a dilution was made into sterile saline 0.85% NaCl w/v, which concentration was standardized by spectrophotometry (600 nm) and poured plate to 9,0 x 108 CFU mL-1 and inoculated with seeds (307,69 mL Kg-1) of simple yellow corn. The percentage of emergency was determined within 7 days. The 10, 30 and 50 days, height was measured and at 50 days the plants were extracted and the weight of dry root and aerial biomass was determined. Enterobacteriaceae increased height (IE = 0.3 - 25.6%), the weight of the root biomass (IE = 2.7 - 129, 7 %%) and air (IE = 0.9 - 89,3%) of corn plants, emphasizing Enterobacter spp.87, 62, 11, Klebsiella sp.85, Pantoea sp.6 and Serratia spp.46 and 84. It showed the potential of bacteria to increase vegetative corn development in greenhouse.